Retaining material

The holding member with a silicone resin and alumina filler in its adhesive member addresses the durability issue of existing electrostatic chucks by enhancing the adhesive's resistance to stress, enabling long-term use under high holding stress.

JP7663740B1Active Publication Date: 2025-04-16NITERRA CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024060672
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-04-04
Publication Date
2025-04-16
Estimated Expiration
2044-04-04

AI Technical Summary

Technical Problem

Existing electrostatic chucks have adhesive members with low durability against stress, limiting their long-term use.

Method used

A holding member with an adhesive member containing a silicone resin with aromatic hydrocarbon groups in its side chain and a filler mainly composed of alumina, which reduces pseudo crosslinking points and increases the proportion of chemical crosslinking points, enhancing durability.

Benefits of technology

The holding member achieves significantly increased breaking time under stress, allowing for long-term use even when the holding stress is close to the adhesive's breaking limit, thereby providing excellent durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007663740000001_ABST
    Figure 0007663740000001_ABST
Patent Text Reader

Abstract

To provide a holding member having excellent durability and capable of being used for a long time. [Solution] A retaining member comprising a first member, a second member, and an adhesive member that bonds the first member and the second member, wherein when the first member and the second member are pulled with a constant tensile load along the connection direction in which the first member and the second member are connected via the adhesive member under a temperature condition of 120°C, the stress generated in the adhesive member when the first member and the second member are pulled with a constant tensile load along the connection direction in which the first member and the second member are connected via the adhesive member is defined as the retaining stress (MPa), and the time from when the retaining stress (MPa) begins to be applied to the adhesive member until the adhesive member breaks is defined as the breakage time (h), the change in the value of the retaining stress (MPa) that increases the common logarithm of the breakage time (h) by 1 is a value within the range of -0.09 MPa or more and less than 0 MPa.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a retaining member. [Background technology]

[0002] As a holding member for holding an object, an electrostatic chuck that holds the object, a wafer, by electrostatic attraction is known. For example, Patent Documents 1 and 2 disclose an electrostatic chuck that includes a base member made of metal, a ceramic member made of ceramic, and an adhesive member that bonds the base member and the ceramic member. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent No. 6611743 [Patent Document 2] Patent No. 6886440 Summary of the Invention [Problem to be solved by the invention]

[0004] However, neither of the techniques of Patent Documents 1 and 2 takes into consideration the durability of the adhesive member against the stress applied to the adhesive member when the base member and the ceramic member are pulled. A holding member with low durability against such stress may be limited in long-term use. For this reason, there has been a demand for the development of a holding member with excellent durability.

[0005] The present invention has been made to solve at least part of the above-mentioned problems, and has an object to provide a holding member having excellent durability that allows for long-term use. [Means for solving the problem]

[0006] The present invention has been made to solve at least part of the above-mentioned problems, and can be realized in the following forms.

[0007] (1) According to one aspect of the present invention, there is provided a retaining member, comprising a first member, a second member, and an adhesive member that bonds the first member and the second member, and when the first member and the second member are pulled with a constant tensile load along a connection direction in which the first member and the second member are connected via the adhesive member under a condition of a temperature of 120° C., the stress generated in the adhesive member when the first member and the second member are pulled with a constant tensile load along the connection direction in which the first member and the second member are connected via the adhesive member is defined as a retaining stress (MPa), and the time from when the retaining stress (MPa) starts to be applied to the adhesive member until the adhesive member breaks is defined as a breaking time (h), the amount of change in the value of the retaining stress (MPa) when the common logarithm of the breaking time (h) is increased by 1 is a value within a range of −0.09 MPa or more and less than 0 MPa.

[0008] According to this configuration, it is possible to provide a retaining member having an adhesive member in which the amount of change in the value of the retention stress (MPa) that increases the common logarithm of the time to break (h) by 1 is within the range of -0.09 MPa or more and less than 0 MPa. Therefore, since the amount of change in the common logarithm of the time to break (h) when the value of the retention stress (MPa) is changed is relatively large, it is possible to provide a retaining member in which the common logarithm of the time to break (h) increases significantly when the value of the retention stress (MPa) is reduced. In other words, it is possible to provide a retaining member with excellent durability that allows for long-term use even in an environment where a retention stress (MPa) close to the breaking limit is applied.

[0009] (2) In the holding member of the above aspect, the adhesive member may contain a silicone resin having an aromatic hydrocarbon group on at least a portion of the side chain. According to this configuration, since at least a part of the side chain of the silicone resin is provided with an aromatic hydrocarbon group, the occurrence of micro-crystallization or entanglement in the main chain of the silicone resin due to the influence of the steric hindrance of the aromatic hydrocarbon group is reduced, and the number of pseudo crosslinking points present in the adhesive member can be reduced. As a result, the proportion of crosslinking points due to chemical bonds whose bonds are difficult to break when stress is applied in the adhesive member can be increased, while the proportion of pseudo crosslinking points whose bonds are easily broken when stress is applied can be reduced, so that even if a holding stress (MPa) close to the breaking limit of the adhesive member is applied, the time from when the holding stress (MPa) is applied to the adhesive member until the adhesive member breaks can be extended.

[0010] (3) In the holding member of the above aspect, the adhesive member may contain a filler containing alumina as a main component. According to this configuration, the main component of the filler is alumina, which has high hydrophilicity. Therefore, when the resin contained in the adhesive member is a resin with high hydrophobicity (e.g., silicone resin), the difference between the SP value of the resin and the SP value of the filler becomes large, and the larger the difference in SP value, the smaller the number of pseudo crosslinking points in the adhesive member can be. Therefore, since the ratio of crosslinking points by chemical bonds in the adhesive member can be increased while the ratio of pseudo crosslinking points can be decreased, even if a holding stress (MPa) close to the breaking limit of the adhesive member is applied, the time from when the holding stress (MPa) is applied to the adhesive member until the adhesive member breaks can be further extended.

[0011] The present invention can be realized in various forms, for example, in the form of an electrostatic chuck or a vacuum chuck comprising the above-mentioned adhesive member, a semiconductor manufacturing apparatus or a ceramic heater comprising the above-mentioned adhesive member, parts comprising these, and methods for manufacturing these, etc. [Brief description of the drawings]

[0012] [Figure 1] FIG. 2 is an explanatory diagram illustrating a cross-sectional configuration of a holding member according to an embodiment of the present invention. [Diagram 2] FIG. 1 is an explanatory diagram for explaining an SP value. [Diagram 3] FIG. 11 is an explanatory diagram showing the results of evaluating the performance of adhesive members. [Figure 4] FIG. 2 is an explanatory diagram of a test piece used for evaluating the performance of an adhesive member. [Diagram 5] FIG. 1 is an explanatory diagram showing test results when a test piece was used to measure a retaining stress. [Figure 6] FIG. 1 is an explanatory diagram showing the rupture time for each holding stress. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] FIG. 1 is an explanatory diagram showing a schematic cross-sectional configuration of a holding member 1 according to an embodiment of the present invention. The holding member 1 is an electrostatic chuck that attracts and holds a semiconductor wafer W, which is an object, by electrostatic attraction. The arrow shown in FIG. 1 indicates the direction in which the semiconductor wafer W is attracted to the holding member 1. The holding member 1 is used, for example, to fix the semiconductor wafer W in a vacuum chamber of a semiconductor manufacturing device. The holding member 1 includes a ceramic member 10, a base member 20, an adhesive member 30, an electrostatic electrode 40, and a heater electrode 50.

[0014] The ceramic member 10 is a disk-shaped member and is made of ceramics. Examples of materials for forming the ceramic member 10 include aluminum oxide (alumina, Al2O3) and aluminum nitride (AlN), and in this embodiment, the ceramic member 10 is made of alumina. The ceramic member 10 has an adsorption surface 10f. The adsorption surface 10f is a circular surface on the side that adsorbs the semiconductor wafer W.

[0015] The base member 20 is a disk-shaped member having a larger diameter than the ceramic member 10, and is made of metal or various composite materials. The metal forming the base member 20 is preferably Al (aluminum), Ti (titanium), or an alloy thereof. The composite material forming the base member 20 is preferably a composite material obtained by melting and pressurizing an aluminum alloy mainly composed of aluminum into a porous ceramic mainly composed of silicon carbide (SiC). The aluminum alloy contained in the composite material may contain Si (silicon) or Mg (magnesium), or may contain other elements as long as they do not affect the properties, etc.

[0016] A coolant flow path 21 is formed inside the base member 20. When a coolant (e.g., a fluorine-based inert liquid or water) flows through the coolant flow path 21, the base member 20 is cooled. At this time, the ceramic member 10 is also cooled by heat transfer (heat withdrawal) between the base member 20 and the ceramic member 10 via the adhesive member 30, and the semiconductor wafer W adsorbed to the adsorption surface 10f of the ceramic member 10 is also cooled.

[0017] The adhesive member 30 is disposed between the ceramic member 10 and the base member 20, and bonds the ceramic member 10 and the base member 20. The ceramic member 10 and the base member 20 correspond to a first member and a second member bonded to each other via the adhesive member 30. The first member and the second member are used to refer to members bonded to each other via the adhesive member. The adhesive member 30 contains a silicone resin having a phenyl group as an aromatic hydrocarbon group in at least a part of the side chain. In this embodiment, the silicone resin contains 5 mol% of phenyl groups. The adhesive member 30 also contains a filler whose main component is alumina. The main component refers to the component with the highest volumetric content.

[0018] The electrostatic electrode 40 is a disk-shaped member provided inside the ceramic member 10, and is made of a conductive material such as tungsten or molybdenum. The electrostatic electrode 40 generates an electrostatic attractive force on the attraction surface 10f when power is supplied from an external power source (not shown). The semiconductor wafer W is attracted toward the attraction surface 10f by this electrostatic attractive force, and is thereby held on the attraction surface 10f.

[0019] The heater electrode 50 is provided inside the ceramic member 10 and is made of a conductive material such as tungsten or molybdenum. The heater electrode 50 generates heat when power is supplied from an external power source (not shown). This heat warms the ceramic member 10, and the semiconductor wafer W attracted to the attracting surface 10f of the ceramic member 10 is also heated.

[0020] FIG. 2 is an explanatory diagram for explaining the SP value. The SP value is a solubility parameter, and is an index that indicates the hydrophilicity or hydrophobicity of a substance. A substance with a large SP value is highly hydrophilic, and a substance with a small SP value is highly hydrophobic. The double-headed arrows shown in each of FIGS. 2(A) to (C) indicate the difference in SP value for the silicone resin and the filler contained in the adhesive member. In detail, the further to the left the left arrowhead of the double-headed arrow is, the smaller the SP value of the silicone resin in the adhesive member is, and the further to the right the right arrowhead is, the larger the SP value of the filler in the adhesive member is.

[0021] Of the double-headed arrows in FIG. 2(A), the left arrowhead indicates the SP value of the silicone resin (having a phenyl group in part of the side chain) contained in the adhesive member 30, and the right arrowhead indicates the SP value of the filler (mainly made of alumina) contained in the adhesive member 30. That is, FIG. 2(A) shows the difference in SP value for the silicone resin and filler contained in the adhesive member 30 of this embodiment. In contrast, FIGS. 2(B) and (C) show the difference in SP value for the silicone resin and filler contained in the adhesive member of the comparative example. In detail, of the double-headed arrows in FIG. 2(B), the left arrowhead indicates the SP value of the silicone resin (having no phenyl group in the side chain), and the right arrowhead indicates the SP value of the filler (mainly made of alumina). Of the double-headed arrows in FIG. 2(C), the left arrowhead indicates the SP value of the silicone resin (having a phenyl group in part of the side chain) contained in the adhesive member 30, and the right arrowhead indicates the SP value of the filler (mainly made of aluminum nitride). 2(A) to 2(C), the adhesive member 30 of this embodiment has a larger difference between the SP value of the silicone resin and the SP value of the filler compared to the adhesive member of the comparative example. The larger the difference in SP value, the lower the mutual affinity, and the fewer the number of pseudo crosslinking points in the adhesive member. The pseudo crosslinking points are crosslinking points formed pseudo in the silicone resin due to the occurrence of minute crystallization and entanglement due to the strong interaction between the main chains of the silicone resin.

[0022] FIG. 3 is an explanatory diagram showing the results of evaluating the performance of the adhesive member. First, each item shown in "Material" in FIG. 3 will be explained. "○" in the "Silicone resin" row indicates that the silicone resin contained in the adhesive member has a phenyl group in a part of the side chain of the silicone resin, and "×" in the "Silicone resin" row indicates that the silicone resin does not have a phenyl group in the side chain. The "Filler type" row indicates the type of filler contained in the adhesive member. With regard to the type of filler, Al2O3 is alumina, and AlN is aluminum nitride. The "Filler amount" row indicates the volume part of the filler in the adhesive member when the entire adhesive member is taken as 100 volume parts. As shown in FIG. 3, both the adhesive member of the embodiment and the adhesive members of Comparative Examples 1 and 2 contain 44 volume parts of filler and 56 volume parts of silicone resin. The adhesive member of the embodiment corresponds to the adhesive member 30 constituting the holding member 1 described above.

[0023] Next, the "performance evaluation" shown in the "physical properties" in FIG. 3 will be described. In the "performance evaluation", as shown in FIG. 4, a test piece TP is used in which one end of each of two rod-shaped members (a first member 301 and a second member 302) is bonded to each other with an adhesive member 30G (a general term for the adhesive member of the embodiment and the adhesive members of Comparative Examples 1 and 2). Using this test piece TP, the stress generated in the adhesive member 30G when the first member 301 and the second member 302 are pulled with a constant tensile load along the connection direction CD in which the first member 301 and the second member 302 are connected via the adhesive member 30G under a temperature condition of 120° C. is defined as the retained stress (MPa), and the time from when the retained stress (MPa) starts to be applied to the adhesive member 30G until the adhesive member 30G breaks is defined as the break time (h). In detail, the retained stress (MPa) is calculated by dividing the load (N) when the test piece TP is pulled to break by the adhesive area. In the "Performance Evaluation", it was evaluated whether the amount of change in the value of the retention stress (MPa) when the common logarithm of the time to break (h) is increased by 1 was within the range of -0.09 MPa or more and less than 0 MPa. That is, "○" in the "Performance Evaluation" row indicates that the amount of change in the value of the retention stress (MPa) when the common logarithm of the time to break (h) is increased by 1 is within the range of -0.09 MPa or more and less than 0 MPa, and "×" in the "Performance Evaluation" row indicates that the amount of change in the value of the retention stress (MPa) when the common logarithm of the time to break (h) is increased by 1 is not within the range of -0.09 MPa or more and less than 0 MPa. Details will be described with reference to Figs. 5(A) to (C).

[0024] 5(A) to (C) are explanatory diagrams showing test results when the retained stress (MPa) was measured using the test piece TP under the condition of a temperature of 120° C. In FIG. 5(A) to (C), the horizontal axis is log 10 (t / h) is shown. 10 (t / h) is the common logarithm of the time to fracture, where t represents the time to fracture (h). t / h is a dimensionless number obtained by dividing the time to fracture (h) by a unit. For example, when t=10h, t / h=10, and log 10(10)=1. In Fig. 5(A)-(C), the vertical axis indicates the retained stress (MPa). The results shown in Fig. 5(A)-(C) are the results when the first member 301 and the second member 302 are pulled along the connection direction CD at each retained stress (MPa). In this case, the first member 301 and the second member 302 are plate-like members with a length of 20 mm, a width of 10 mm, and a thickness of 10 mm, and the test piece TP is a test piece in which the first member 301 and the second member 302 are bonded with an adhesive member 30G with a thickness of 0.7 mm. The bonding conditions here are appropriately adjusted according to the adhesive member 30G used so as to obtain the desired adhesive properties. For example, the test piece TP can be produced by heating the adhesive member 30G sandwiched between the first member 301 and the second member 302 at 100°C for 72 hours and then further heating at 140°C for 10 hours. The shape of the test piece TP was created with reference to JIS K 6849. As a measuring device for measuring the retained stress (MPa), a known tensile tester or strength tester can be used, for example, Autograph AGS-5kNX manufactured by Shimadzu Corporation.

[0025] The line segment LA shown in FIG. 5(A) is a line segment showing the test results of measuring the rupture time (h) of the test piece TP made using the adhesive member of the embodiment. The line segment LB shown in FIG. 5(B) is a line segment showing the test results of measuring the rupture time (h) of the test piece TP made using the adhesive member of Comparative Example 1. The line segment LC shown in FIG. 5(C) is a line segment showing the test results of measuring the rupture time (h) of the test piece TP made using the adhesive member of Comparative Example 2. The lines LA, LB, and LC correspond to regression lines obtained by the least squares method from the measurement data of multiple rupture times (h) measured using each test piece TP. When the retained stress (MPa) is Hs and the common logarithm of the rupture time (h) is CL, the regression equations representing the regression lines (lines LA, LB, and LC) are as follows. Adhesive member of the embodiment (line segment LA): Hs = -0.0348CL + 0.9347 Adhesive member of Comparative Example 1 (line segment LB): Hs = -0.0967CL + 1.2979 Adhesive member of Comparative Example 2 (line segment LC): Hs = -0.1627CL + 1.4183

[0026] Regarding the regression equation of the adhesive member of the embodiment, the value of Hs changes by -0.0349 for every increase in the value of CL by 1. In other words, the change in the value of the retaining stress (MPa) that increases the common logarithm CL of the rupture time (h) by 1 is -0.0348 (a value within the range of -0.09 MPa or more and less than 0 MPa). On the other hand, regarding the regression equation of the adhesive member of Comparative Example 1 and the regression equation of the adhesive member of Comparative Example 2, the change in the value of the retaining stress (MPa) that increases the common logarithm CL of the rupture time (h) by 1 is not a value within the range of -0.09 MPa or more and less than 0 MPa. In this way, the "performance evaluation" is an evaluation based on the coefficient value of the common logarithm CL of the rupture time (h) in the regression line obtained by the least squares method from the measurement data of multiple rupture times (h) measured using the test piece TP. In other words, if the adhesive member 30G contained in the test piece TP is different, the coefficient and intercept value of the common logarithm CL of the break time (h) in the regression equation will also be different, and the "performance evaluation" is performed based on the coefficient of the common logarithm CL of the break time (h).

[0027] For example, when "performance evaluation" of the adhesive member 30 already included in the holding member 1 described above is performed, it is performed in the following steps. First, a portion including the ceramic member 10, the base member 20, and the adhesive member 30 is cut out from the holding member 1, and a test piece TP is prepared from the cut out portion. At this time, the ceramic member 10 and the base member 20 correspond to the first member 301 and the second member 302 in the test piece TP. Next, using the prepared test piece TP, the rupture time (h) is measured when the first member 301 and the second member 302 are pulled along the connection direction CD at each holding stress (MPa) to obtain multiple measurement data, and then a regression equation representing a regression line obtained by the least squares method is created from the multiple measurement data. Then, "performance evaluation" is performed based on the value of the coefficient of the common logarithm CL of the rupture time (h) in the regression equation. The shape of the test piece for performing the "performance evaluation" is not limited to the shape of the test piece TP, and may be any shape as long as the first member 301 and the second member 302 bonded via the adhesive member 30 can be pulled along the connection direction CD. In addition, in the test piece for performing the "performance evaluation", the thickness of the adhesive member 30G is preferably 0.7 mm, but since the effect of the thickness on the "performance evaluation" is small, even if the thickness of the adhesive member 30G is different from 0.7 mm, it is possible to measure the rupture time (h) when the first member 301 and the second member 302 are pulled and regard it as "performance evaluation".

[0028] 3, as a result of evaluating the adhesive member of the Example and the adhesive members of Comparative Examples 1 and 2, only the adhesive member of the Example received a "performance evaluation" of "○". The reason that the adhesive member of the Example (corresponding to the adhesive member 30 constituting the holding member 1 described above) received a "performance evaluation" of "○" is considered to be because the adhesive member of the Example contained a silicone resin having a phenyl group (5 mol%) as an aromatic hydrocarbon group in part of the side chain, and a filler mainly composed of alumina.

[0029] FIG. 6 is an explanatory diagram showing the rupture time (h) for each retaining stress (MPa). The line segment La shown in FIG. 6 is a line segment showing the rupture time (h) corresponding to each retaining stress (MPa) using the regression equation showing the above-mentioned line segment LA (see FIG. 5). The line segments Lb and Lc shown in FIG. 6 are line segments showing the rupture time (h) corresponding to each retaining stress (MPa) using the regression equation showing the above-mentioned line segments LB and LC (see FIG. 5). In FIG. 6, the horizontal axis shows the retaining stress (MPa) at each ratio when the retaining stress (MPa) when the test piece TP produced using each adhesive member 30G immediately breaks is set to 100%. In FIG. 6, the vertical axis shows the rupture time (h).

[0030] As shown by point Pa on line segment La, it was confirmed that the test piece TP made using the adhesive member of the embodiment had a rupture time (h) of 10000h (=1.E+04) or more when the retention stress (MPa) was about 74% or less of the retention stress (MPa) at the time of immediate rupture. On the other hand, as shown by point Pb on line segment Lb, it was confirmed that the test piece TP made using the adhesive member of comparative example 1 had a rupture time (h) of 10000h or more when the retention stress (MPa) was about 55% or less of the retention stress (MPa) at the time of immediate rupture. In addition, although not shown on line segment Lc, it was confirmed that the test piece TP made using the adhesive member of comparative example 2 had a rupture time (h) of 10000h or more when the retention stress (MPa) was about 38% or less of the retention stress (MPa) at the time of immediate rupture.

[0031] In addition, it was confirmed that the rupture time (h) when a 90% retention stress (MPa) was applied relative to the retention stress (MPa) at the time of immediate rupture was about 0.227 h in the example, about 0.010 h in the comparative example 1, and about 0.003 h in the comparative example 2. On the other hand, it was confirmed that the rupture time (h) when a 70% retention stress (MPa) was applied relative to the retention stress (MPa) at the time of immediate rupture was about 294090 h in the example, about 27 h in the comparative example 1, and about 1 h in the comparative example 2. That is, it was confirmed that the rupture time (h) was the longest in the test piece TP produced using the adhesive member of the example and the shortest in the test piece TP produced using the adhesive member of the comparative example 2, regardless of the retention stress (MPa) applied. These results are probably due to the fact that, in the adhesive member of the Example, the change in the value of the retained stress (MPa) when the common logarithm of the time to break (h) increases by 1 is within the range of -0.09 MPa or more and less than 0 MPa, and therefore, compared to the adhesive members of Comparative Examples 1 and 2, when the value of the retained stress (MPa) is reduced (when the retained stress (MPa) at the time of immediate break is reduced to 90% and 70%), the common logarithm of the time to break (h) increases significantly (see FIG. 6). Therefore, it was confirmed that the adhesive member of the Example can be used for a long time at a retained stress (MPa) close to the time to immediate break, and has excellent durability.

[0032] In the adhesive member 30 (the adhesive member of the embodiment) included in the holding member 1 of the embodiment described above, the change in the value of the holding stress (MPa) that increases the common logarithm of the rupture time (h) by 1 is a value within the range of -0.09 MPa or more and less than 0 MPa. Therefore, in such an adhesive member 30, the change in the common logarithm of the rupture time (h) when the value of the holding stress (MPa) is changed is relatively large, so that it is possible to provide a holding member 1 in which the common logarithm of the rupture time (h) increases significantly when the value of the holding stress (MPa) is reduced. In other words, it is possible to provide a holding member 1 with excellent durability that can be used for a long time even in an environment where a holding stress (MPa) close to the rupture limit is applied. The holding stress (MPa) close to the rupture limit here means a stress close to the holding stress (MPa) at the time of immediate rupture.

[0033] Moreover, the adhesive member 30 (the adhesive member of the embodiment) provided in the holding member 1 contains a silicone resin having a phenyl group as an aromatic hydrocarbon group in a part of the side chain. Therefore, the occurrence of micro-crystallization and entanglement in the main chain of the silicone resin is reduced due to the influence of the steric hindrance of the aromatic hydrocarbon group, and the number of pseudo crosslinking points present in the adhesive member 30 can be reduced. As a result, in the adhesive member 30, the proportion of crosslinking points due to chemical bonds whose bonds are difficult to break when stress is applied can be increased, while the proportion of pseudo crosslinking points whose bonds are easily broken when stress is applied can be reduced. Therefore, even if a holding stress (MPa) close to the breaking limit of the adhesive member 30 is applied, the time from when the holding stress (MPa) is applied to the adhesive member 30 until the adhesive member 30 breaks can be extended.

[0034] In addition, in the adhesive member 30 (adhesive member of the embodiment) included in the holding member 1, the main component of the filler is alumina with high hydrophilicity. In addition, since the resin included in the adhesive member 30 is a silicone resin with high hydrophobicity, the difference between the SP value of the resin and the SP value of the filler is large, so that the number of pseudo crosslinking points can be reduced. Therefore, since the ratio of crosslinking points due to chemical bonds can be increased while the ratio of pseudo crosslinking points can be reduced in the adhesive member 30, even if a holding stress (MPa) close to the breaking limit of the adhesive member 30 is applied, the time from when the holding stress (MPa) is applied to the adhesive member 30 until the adhesive member 30 breaks can be further extended. As in the above-mentioned embodiment, when the silicone resin has an aromatic hydrocarbon group in a part of the side chain, the hydrophobicity is higher than when the silicone resin does not have an aromatic hydrocarbon group (see FIG. 2), and the difference with the SP value of the filler is larger, which is preferable.

[0035] <Modifications of this embodiment> The present invention is not limited to the above-described embodiment, and can be embodied in various forms without departing from the spirit and scope of the invention. For example, the following modifications are also possible.

[0036] In the above embodiment, the silicone resin in the adhesive member 30 contains 5 mol % of phenyl groups, but is not limited thereto. The proportion of phenyl groups contained in the silicone resin may be any proportion, and is preferably within a range of 3 mol % or more and 16 mol % or less. In the above embodiment, the silicone resin in the adhesive member 30 has phenyl groups in at least a part of its side chain, but is not limited thereto. For example, the side chain of the silicone resin may have an aryl group such as a tolyl group, a xylyl group, or a naphthyl group instead of or in addition to the phenyl group. Of course, it is preferable that the side chain of the silicone resin has at least a phenyl group.

[0037] In the above embodiment, the filler in the adhesive member 30 may include carbon black. The filler may include carbon powder such as carbon fiber, carbon nanotube, and graphene instead of or in addition to carbon black.

[0038] In the above embodiment, the adhesive member 30 contains a silicone resin and a filler, but is not limited thereto. The adhesive member 30 may contain other components in addition to the silicone resin and the filler. Examples of the other components include a reaction inhibitor, a viscosity adjuster, and a heat resistance improver. The heat resistance improver is preferably one having a radical scavenging ability, and carbon black is particularly preferable.

[0039] Although the present aspect has been described above based on the embodiment and modified examples, the above-mentioned embodiment of the aspect is intended to facilitate understanding of the present aspect and does not limit the present aspect. The present aspect may be modified or improved without departing from the spirit and scope of the claims, and equivalents are included in the present aspect. Furthermore, if a technical feature is not described as essential in this specification, it may be deleted as appropriate. [Explanation of symbols]

[0040] 1...Retaining member 10...Ceramics components 10f…Adsorption surface 20...Base member 21... Coolant flow path 30, 30G…Adhesive material 40...Electrostatic electrode 50…Heater electrode 301…First member 302...Second member

Claims

[Claim 1] A retaining member, A first member made of alumina; A second member; and an adhesive member that bonds the first member and the second member, the adhesive member includes a silicone resin having an aromatic hydrocarbon group in at least a part of a side chain, and a filler containing hydrophilic alumina as a main component, A retaining member characterized in that, when the stress generated in the adhesive member when the first member and the second member are pulled with a constant tensile load along the connection direction in which the first member and the second member are connected via the adhesive member under a condition of a temperature of 120°C is defined as a retaining stress (MPa), and the time from when the retaining stress (MPa) begins to be applied to the adhesive member until the adhesive member breaks is defined as a breaking time (h), the amount of change in the value of the retaining stress (MPa) that increases the common logarithm of the breaking time (h) by 1 is a value within the range of -0.09 MPa or more and less than 0 MPa.

Citation Information

Patent Citations

  • Method for fabricating electrode pattern made of conductive silicone rubber, all-silicone rubber electrostatic chuck, and method for manufacturing the same

    JP2015079863A

  • Composite member, holding device, and bonding structure

    JP2022109651A

  • Composite materials

    JP6611743B2

  • Composite member and adhesive composition

    JP6886440B2